Evaluasi Penyaluran Pupuk Bersubsidi Di Kelurahan Ranowangko Kecamatan Tondano Timur Kabupaten Minahasa - Walangare, Miranda Evryl; Waney, Nordy Fritsgerald Lucky; Montolalu, Maya Hendrietta (AGRI-SOSIOEKONOMI, 2024)
This research aims to analyze the effectiveness and evaluate the distribution of subsidized fertilizer in Ranowangko Village, East Tondano District, Minahasa Regency based on the "6 Right" principles, namely right quantity, right place, right type, right price, right quality and right time. This research will last for 3 months, namely April-June 2024. Primary data was obtained through data collection using the sample survey method and secondary data was obtained from related agencies. The sampling method uses a purposive sampling technique by determining the number of samples using the Slovin Formula. The data analysis method used to measure effectiveness uses the Guttman scale and evaluation uses descriptive data analysis techniques. The research results show that the right place, right type and right quality indicators are categorized as very effective. Furthermore, the indicators for the right amount and time are categorized as quite effective. Then the exact price indicator is categorized as ineffective.